Imaging biomarkers of vascular and axonal injury are spatially distinct in chronic traumatic brain injury. Issue 8 (August 2021) - Haber, Margalit; Amyot, Franck; Lynch, Cillian E; Sandsmark, Danielle K; Kenney, Kimbra; Werner, John K; Moore, Carol; Flesher, Kelley; Woodson, Sarah; Silverman, Erika; Chou, Yiyu; Pham, Dzung; et al.
Traumatic Brain Injury (TBI) is associated with both diffuse axonal injury (DAI) and diffuse vascular injury (DVI), which result from inertial shearing forces. These terms are often used interchangeably, but the spatial relationships between DAI and DVI have not been carefully studied. Multimodal magnetic resonance imaging (MRI) can help distinguish these injury mechanisms: diffusion tensor imaging (DTI) provides information about axonal integrity, while arterial spin labeling (ASL) can be used to measure cerebral blood flow (CBF), and the reactivity of the Blood Oxygen Level Dependent (BOLD) signal to a hypercapnia challenge reflects cerebrovascular reactivity (CVR). Subjects with chronic TBI (n = 27) and healthy controls (n = 14) were studied with multimodal MRI. Mean values of mean diffusivity (MD), fractional anisotropy (FA), CBF, and CVR were extracted for pre-determined regions of interest (ROIs). Normalized z-score maps were generated from the pool of healthy controls. Abnormal ROIs in one modality were not predictive of abnormalities in another. Approximately 9-10% of abnormal voxels for CVR and CBF also showed an abnormal voxel value for MD, while only 1% of abnormal CVR and CBF voxels show a concomitant abnormal FA value. These data indicate that DAI and DVI represent two distinct TBI endophenotypes that are spatially independent.